PENGARUH SUKU BUNGA DEPOSITO, KURS, DAN INFLASI TERHADAP SIMPANAN DANA PIHAK KETIGA PADA BANK UMUM DI INDONESIA TAHUN 2015 – 2019 - Widiasti, Yuni; Hadi, Syamsul (Program Studi Ekonomi Pembangunan, 2022)
This study aims to determine whether there is a significant effect between deposit interest rates, exchange rates, inflation on deposits of third party funds at commercial banks in Indonesia in 2015-2019. The data analysis method used is multiple linear analysis technique with a significance level of 0.05, F-test for simultaneous or simultaneous testing and t-test for partial testing. The results showed that simultaneously deposit interest rates, exchange rates, inflation had a significant effect on deposits of third party funds. While partially, the deposit interest rate has a significant negative effect on deposits of third party funds, the exchange rate has a significant positive effect, inflation has a significant negative effect on deposits of third party funds.